Nominal rigidities and the dynamic effects of a monetary shock - Rafael Gerke (Technische Universität Darmstadt, Department of Law and Economics, 2001)
Two dynamic sticky price models with monopolistic competition in the goods market are presented. In the first model, each intermediate goods producer faces quadratic costs of adjusting its nominal price as introduced by Rotemberg (1982); the second model incorporates staggered price setting as proposed by Taylor (1980) and recently discussed by Chari/Kehoe/McGrattan (2000). Using the approximation method and the toolkit of Uhlig (1999) these models are used to derive theoretical impulse response functions. One aim is to check whether these two different forms of nominal price rigidities imply quantitatively and qualitatively different impulse response functions. Interestingly, both models do not seem to imply as much persistence as empirical impulse response functions typically indicate. However, qualitative differences do exist.
Keywords: 330; Konjunkturtheorie; Monopolistischer Wettbewerb; Preisrigidität; Geldpolitik; Schock; Geldpolitische Transmission; Vergleich; Theorie